Embedding responsible innovation within synthetic biology research and innovation: insights from a UK multi-disciplinary research centre. Issue 3 (1st September 2020) - Pansera, Mario; Owen, Richard; Meacham, Darian; Kuh, Vivienne
ABSTRACT: Over the last decade the discourse of responsible innovation (RI) has become a significant feature of debates concerning the relationships between science, innovation and society in the fields of biosciences and biotechnologies. We document how this discourse has evolved over the period 2014–2019 at a Synthetic Biology Research Centre hosted within a University in the UK (BrisSynBio). We describe how an approach to RI has evolved to include but go beyond public engagement, by encouraging practices aimed at anticipation, reflexivity and deliberation in sometimes creative and innovative ways. We describe how the Centre has struggled to capture the impacts of RI interventions on the everyday practices and behaviours of scientists and the outcomes of their work. The study reveals the importance of leadership, creativity, innovation, institutional support, openness to change and mechanisms of capturing impact for successful RI institutionalisation.